From the mat to mastery: a Judoka’s quest in the wake of injury – professional Judokas’ experiences of suffering an anterior cruciate ligament injury - Andreas Ivarsson; Eric Hamrin Senorski; Kristian Samuelsson; Martin Hägglund; Robert Prill; Hans-Christer Holmberg; Ramana Piussi; Moa Engström (BMJ Open Sport & Exercise Medicine)
This study explored professional Judokas’ experiences of the anterior cruciate ligament (ACL) injury process, the consequences of the injury, and their perceptions of underlying factors contributing to the injury. Eleven professional Judokas treated with ACL reconstruction were interviewed using semi-structured interviews. Qualitative content analysis of the transcripts revealed two main themes: ‘from the mat to mastery: a Judoka’s quest in the wake of injury’ and ‘beyond the physical: the silent struggle for psychological victory.’ Judokas described judo as a lifestyle, with their injuries impacting both physical performance and mental health. Fatigue, high training intensity, and bad luck were identified as contributing factors to their injuries. While the injury posed significant physical and mental challenges, Judokas emphasized the role of the discipline and structure learned through judo to navigate the recovery process. Judokas attributed their ACL injuries to a mix of preparation and unpredictable elements, and reported both positive and negative consequences of their experiences.